FACTORS THAT EFFECT EMPLOYEE PRODUCTIVITY WITH WORK COMPETENCY AS INTERVENING VARIABLE AT FOOD AND BEVERAGE MSMEs IN BATAM - Mischelle Lo; Agustinus Setyawan (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
Labour is one of the most important things in measuring the competitiveness of a country. Indonesia's workforce is ranked 51 out of 63 studied by the International Institute for Management Development (IMD) in the World Talent Ranking in 2022. This can be seen based on statistical data on the level of labour productivity released in 2022 by the ILOSTAT (International Labor Organization) agency that Indonesia is still in 107th place out of 185 countries at US $ 13.1 per hour. This study was conducted to examine the effect of work discipline and work motivation on employee productivity with work competence as mediation in Food and Beverage MSMEs in Batam. The research method used is a quantitative approach. The research collected respondents using a questionnaire method through gform for 400 samples. The data were analyzed using SPSS to analyze descriptive data and Smart PLS to test research hypotheses. The results showed that the variables of work discipline and work motivation directly affect employee productivity and indirectly affect through work competency.